“Crochetage” (Notch) on R wave in inferior limb leads: A new independent electrocardiographic sign of atrial septal defect - Heller, Joseph; Hagège, Albert A.; Besse, Bruno; Desnos, Michel; Marie, François-Noël; Guerot, Claude (Journal of the American College of Cardiology, 1996)
Objectives. This study sought to determine the clinical significance of a “crochetage” pattern—a notch near the apex of the R wave in electrocardiographic (ECG) inferior limb leads—in secundum atrial septal defect. Background. Atrial septal defect is often overdiagnosed on the basis of classical clinical features. Thus, more specific signs on the ECG for screening are needed. Methods. We searched for a crochetage pattern in 1,560 older children and adults: 532 with secundum atrial septal defect, 266 with ventricular septal defect, 146 with pulmonary stenosis, 110 with mitral stenosis, 47 with cor pulmonale and 459 normal subjects. Results. This pattern was observed respectively in 73.1%, 35.7%, 23.3%, 6.4%, 10.6% and 7.4% of these groups (p < 0.001). In atrial septal defect, its incidence increased with larger anatomic defect (p < 0.0001) or greater left-to-right shunt (p < 0.0001), even in the presence of pulmonary hypertension. By multiple regression analysis, only shunt size (p < 0.0006) and defect location (p < 0.0001) were the determinants of its presence. In all groups, the specificity of this sign for the diagnosis was remarkably high when present in all three inferior limb leads (≥92%), even when comparison was limited to patients with an incomplete right bundle branch block (≥95.2%). Early disappearance of this pattern was observed in 35.1% of the operated-on patients although the right bundle branch block pattern persisted. Conclusions. A crochetage pattern of the R wave in inferior limb leads is frequent in patients with atrial septal defect, correlates with shunt severity and is independent of the right bundle branch block pattern. Sensitivity and specificity of this sign are remarkably high when it is associated with an incomplete right bundle branch block or present in all inferior limb leads.